Maintaining the fight for equality through and beyond COVID-19: a focus on the build back better report and ambidextrous leadership. Issue 1 (19th November 2020) - Smith, Simon M.; Butler, Steve
Abstract : Purpose: The purpose of this paper is to explore the Diversity Project's Build Back Better report, which considers leadership practice while maintaining the fight for equality through and beyond COVID-19, through the lens of ambidextrous leadership. Design/methodology/approach: The authors succinctly present findings from the Build Back Better report that explores an industry response of investment and savings practitioners to managing diversity and inclusion through and beyond COVID-19. Ambidextrous leadership is applied to the discussion to offer greater theoretical discussion and practical consideration for HR leaders and their strategic approaches to the subject at hand. Findings: The Build Back Better report offers numerous recommendations for leadership practice within these unprecedented times. An ambidextrous leadership approach can assist in supporting many of the recommendations, as they are complex and potentially paradoxical. Originality/value: The Build Back Better report offers a practitioner's immediate response to supporting business leaders shape their strategies as national lockdown periods ease while also ensuring the fight for equality is not lost within the COVID-19 crisis.